Opinion 2438: Bolitophagus cornutus Fabricius, 1801 (currently Bolitotherus cornutus; Insecta, Coleoptera, Tenebrionidae): precedence granted over Opatrum bifurcum Fabricius, 1798 - ICZN (Bulletin of Zoological Nomenclature, 2019)
The International Commission on Zoological Nomenclature has conserved the specific name of Bolitophagus cornutus Fabricius, 1801 (currently Bolitotherus cornutus) by giving it precedence over its senior subjective synonym Opatrum bifurcum Fabricius, 1798.
Keywords: Nomenclature; taxonomy; Coleoptera; Tenebrionidae; Bolitotherus; Opatrum bifurcum; Bolitophagus cornutus; North America